Umbral Methods and Harmonic Numbers - Giuseppe Dattoli (Axioms, 2018)
The theory of harmonic-based functions is discussed here within the framework of umbral operational methods. We derive a number of results based on elementary notions relying on the properties of Gaussian integrals.